Effect of the addition of polyester-grafted-cellulose nanocrystals on the shape memory properties of biodegradable PLA/PCL nanocomposites. (June 2018) - Sessini, Valentina; Navarro-Baena, Iván; Arrieta, Marina P.; Dominici, Franco; López, Daniel; Torre, Luigi; Kenny, José M.; Dubois, Philippe; Raquez, Jean-Marie; Peponi, Laura
Abstract: In this work the thermally-activated shape memory response of biodegradable nanocomposites based on PLA/PCL blend reinforced with different type of cellulose nanocrystals has been reported, and compared with those of the neat matrix, at the same transition temperature of 55 °C and at the same different deformations, 50%, 100% and 150%. In particular, cellulose nanocrystals have been synthesized and then functionalized by "grafting from" reaction by ring opening polymerization of both PLLA and PCL using the OH groups onto the cellulose nanocrystals surface as initiators for the reaction. The morphology, thermal and mechanical analysis have been performed in order to obtain the parameters for the thermo-mechanical shape memory cycles. Moreover, the addition of the CNC-based nanofillers on the compatibility of PLA-PCL blends in 70:30 proportion has been evaluated. All the biodegradable nanocomposite formulations showed excellent shape memory response, similar to those of the neat matrix, with strain recovery ratio and strain fixity ratio higher than 80% and 90%, respectively. This fact indicates that in this case, the shape memory response of the nanocomposites is mainly controlled by the response of the neat blend and they are slightly influenced by the increase of compatibility between the components of the blend. In addition, all nanocomposite films were fully disintegrated under composting conditions confirming their biodegradable nature, obtaining that the presence of CNC-based nanofillers speeds up the disintegration rate of the nanocomposites in comparison with the pure matrix. Highlights: Cellulose nanocrystals were functionalized with different chemical modifications, grafting PLLA and PCL chains onto their surface. The effect of CNC-based nanofillers in the thermally-activated shape memory behavior of PLA/PCL blend was studied. The disintegrability test confirmed the biodegradable character of these nanocomposites for biomedicine or food packaging.